Genetic variation of allergic disease is associated with the susceptibility to COVID-19. Issue 5 (May 2022) - Xu, Yaqi; Gao, Ran; Zhu, Gaizhi; Zhou, Shan; Li, Huan; Su, Wenting; Han, Gencheng; Wang, Renxi
Highlights: Seventy-four genetic variations were got from the largest allergic disease GWAS. Genetic variation of allergic disease reduces the susceptibility to COVID-19. The effect of genetic variations on COVID-19 is robust without obvious bias.